Destination leadership: Leadership for territorial development - Kozak, M.; Volgger, M.; Pechlaner, Harald (Emerald Group Publishing Limited, 2014)
Tourist destinations often coincide with the most beautiful and attractive places. However, these places tend to be particularly sensitive, either from a natural or cultural point of view (or both). Additionally, quite different types of territories attract tourists – from peripheral regions to the largest city centers in the world. Thus, destination leadership must mean dealing with these diverse but, certainly always, sensitive environments. This requires balancing daring and progressive pproaches with more conservative strategies. Destination leadership means interpreting the various and specific natural and cultural contexts and plotting tailor-made future development paths. Therefore, it may be necessary to speak about Alpine destination leadership (Pechlaner and Volgger, 2014), island destination leadership, city destination leadership, and so on. We can summarize these thoughts by stating that destination leadership is about proactively shaping the future development of territories. Without doubt, this development needs to respect and thoroughly consider local networks and the history of these networks.